Demand for white meats among working households of a tertiary institution in Nigeria - Adeola Obayelu Oluwakemi; Damilare Odetola Peter (Western Balkan Journal of Agricultural Economics and Rural Development, 2022)
White meat is associated with lower cholesterol level, reduction in cardiovascular diseases and more protein content than red meat. Owing to a paucity of empirical studies on its demand in Nigeria, this study assessed household demand for selected white meats among the staff of University of Ibadan. Elasticities of demand were estimated with Quadratic Almost Ideal Demand System (QUAIDS). Chicken, Turkey and snail meats were necessity goods, while fish, duck, rabbit, Guinea fowl and quail meats were luxury goods. All the white meat types were normal goods with the exception of snail and duck meats that were considered as inferior goods. The selected white meats were mainly gross complements but a few were substitutes. Own-and cross-prices, age, gender, educational attainment and household size explained demand for white meat among the working households. Price reduction and income policies that would increase the purchasing power of the working households are viable policy thrusts to enhance their demand for white meats.